Performance analysis of multiple-beam WDM free space laser-communication system using homodyne detection approach. Issue 2 (February 2023) - Gupta, Yogesh Kumar; Goel, Aditya
Abstract: A free space optical module is used in laser communication to transport a signal from the transmitter to the receiver. Free Space Optical Communication (FSOC) is a Line of Sight connectivity that sends a highly narrow beamwidth. FSOC provides high bandwidth and data rates greater than 10 Gbps. Although FSOC technology has several advantages, it is inefficient for long-distance transmission because of many constraints caused by atmospheric variables. In FSOC connections, turbulence-induced scintillation is a severe problem that significantly reduces link performance. Keeping this problem in mind, the objective of this study is to enhance FSOC performance in terms of energy efficiency, spectral efficiency and long-distance transmission. To achieve this, a study is employed using a hybrid combination of Higher-order Gaussian filter (HGF), post-amplification and a homodyne detection method. Precisely, the simulative study of 32-channel wavelength division multiplexing (WDM) FSOC has used channel model Gamma-Gamma with single-beam (SB), dual-beam (DB), four multiple-beam (MB4) and eight multiple-beam (MB8) techniques. The proposed framework has achieved a Channel capacity of more than 320 Gbps. The transmission range enhancement of 112% and reduction in transmitted power of 100% are achieved, which are considerably more significant compared with state-of-the-art literature studies. The OptiSystem platform is used to gather the outcomes. The performance is based on parametric analysis of bit error rate (BER), Quality (Q) factor and eye height.